Evaluation of haptoglobin phenotypes in acute myocardial infarction (AMI) and their association with some risk factors - H. A. Khazaei; H. Harati; A. Bolouri; A. Nakhaei; M. Mohammadi; F. Nazari; M. Noura; A. Khazaei; B. Khazaei; O. Dadras; M. Atabaki; V. Kalati (Медицинская иммунология, 2020)
Acute myocardial infarction (AMI) is one of the most common cardiovascular complications with a complex pathogenesis where inflammatory markers are involved in disease etiology. The aim of this study was to investigate haptoglobin phenotypes and their association with some risk factors in patients with a history of AMI. 120 patients who were referred to the emergency department of Amir Al Momenin hospital of Zahedan city, Zahedan-Iran were recruited in a cross-sectional case control study. 120 normal individuals were also chosen as controls for this study. Serum was isolated from routine bloods taken for diagnostic tests and used to determine haptoglobin phenotype distribution by electrophoresis. Phenotype differences as percent of phenotype frequency in patient and control groups were analysed using the χ2 test and SPSS software. A high frequency of serum Hp2-2 haptoglobin phenotype in patients and healthy control were found (62.5% and 58.3% respectively). A meaningful statistical correlation between high frequency of Hp2-2 haptoglobin phenotype and AMI was not found (p value = 0.484). Whereas high frequency of Hp1-1 and HP2-2 phenotypes was associated with hyperlipidemia and hypertension respectively (p value = 0.01 and 0.04). Our results showed that there was a high frequency of Hp2-2 haptoglobin phenotype in patients as well as healthy controls in the population studies. High frequencies of Hp1-1and Hp2-2 phenotypes were associated with AMI in patients with hyperlipidemia and hypertension respectively. Thus these phenotypes in AMI patients may modulate the inflammatory response in combination with hyperlipidemia and hypertension.